Vandetanib in advanced non small cell lung cancer: a promise unfulfilled - de Boer, Richard H. (Translational Lung Cancer Research; Vol 2, No 1 (February 14, 2013): Translational Lung Cancer Research, 2012)
Despite a number of recent advances in the management of advanced non-small-cell lung cancer (NSCLC), survival rates remain poor compared with the other major malignancies. Standard chemotherapy leads to modest response rates and survival benefits and therapeutic results appear to have reached a plateau, although maintenance chemotherapy appears to be of benefit (1). Subsequently, the last decade has seen a major shift in research focus towards identifying molecular targets, developing targeted therapeutics, and validating biomarkers so to improve treatment outcomes.